1997
DOI: 10.1029/97gl01560
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of ClONO2 with HCl on aluminum oxide

Abstract: Abstract. The chlorine activation reaction C1ONO2 + HC1 • HNO3 + C12 was investigated in the laboratory on hydroxylated a-alumina surfaces under reactant partial pressure, humidity, and temperature conditions coveting those which are encountered at mid-latitudes in the lower stratosphere. The measured reaction probability is T ~ 0.02. This result has implications with regard to the stratospheric impact of launch vehicles utilizing solid-fuel rocket motors (SRMs), such as the Space Shuttle. The exhaust from SRM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
112
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 27 publications
0
112
0
Order By: Relevance
“…Therefore, the heterogeneous reactions of TiO 2 with chlorine containing trace gases (e.g., ClONO 2 , HOCl, and HCl) in the stratosphere need to be investigated before we can fully assess the impact of TiO 2 on stratospheric ozone. One previous study (Molina et al, 1997) investigated the uptake of ClONO 2 (1-10 × 10 −7 Torr) onto aluminum oxide and Pyrex glass in the presence of HCl (1-10 × 10 −6 Torr) at 210-220 K, and suggested that this process is very efficient, with an uptake coefficient of 0.02, which is > 10 times larger than that onto stratospheric sulfuric acid aerosols. In addition, the uptake of N 2 O 5 onto HCldoped sulfuric acid and SiO 2 (Raff et al, 2009) leads to the formation of ClNO 2 , whose photolysis will release Cl atoms and therefore represent a pathway for chlorine activation (Ghosh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the heterogeneous reactions of TiO 2 with chlorine containing trace gases (e.g., ClONO 2 , HOCl, and HCl) in the stratosphere need to be investigated before we can fully assess the impact of TiO 2 on stratospheric ozone. One previous study (Molina et al, 1997) investigated the uptake of ClONO 2 (1-10 × 10 −7 Torr) onto aluminum oxide and Pyrex glass in the presence of HCl (1-10 × 10 −6 Torr) at 210-220 K, and suggested that this process is very efficient, with an uptake coefficient of 0.02, which is > 10 times larger than that onto stratospheric sulfuric acid aerosols. In addition, the uptake of N 2 O 5 onto HCldoped sulfuric acid and SiO 2 (Raff et al, 2009) leads to the formation of ClNO 2 , whose photolysis will release Cl atoms and therefore represent a pathway for chlorine activation (Ghosh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, there has been little data on which to base such a model. Molina et al [1997] measured the rate of the chlorine activation reaction C1ONO2 + HC1 --> HNO3 + C12 on alumina surface and noted that the reaction was fast enough so as to raise the possibility that AAGTO might be reduced by chlorine activation on SRM alumina surface as much, or more than, the reduction from SRM chlorine loading alone. Jackman et al [1998] coupled the Goddard Space Flight Center two-dimensional photochemistry and transport model, the chlorine activation rates reported by Molina et al [ 1997], and various models of the size distribution of alumina to Copyright 1999 by the American Geophysical Union.…”
Section: Introductionmentioning
confidence: 99%
“…Several major field campaigns of air quality studies, such as the Program of Regional Integrated Experiments of Air Quality in the Pearl River Delta (PRIDE-PRD) 2004 and 2008 , have been conducted in this region to monitor the pollution situation and characterize the chemical and meteorological conditions responsible for accumulations of gaseous and PM pollutants of primary and secondary origins. In addition to their effects on visibility, human health, and weather and regional climate, pollution aerosols profoundly impact atmospheric chemistry via multiphase processes (Molina et al, 1997;Zhang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%